A MODEL PROPOSAL AND DISCUSSION ON THE EFFECT OF INFORMAL ECONOMY ON TURKISH SERVICE EXPORT IN THE GLOBALIZATION PROCESS - Bilgiç, Emre (Bursa Teknik Üniversitesi, 2019)
Undoubtedly, globalization is a phenomenon which is influential on each field. In this sense, informal economy is also one of the areas affected by globalization process. On the other hand, especially after 2000s, with the beginning of separately examination of trade in goods and trade in services, factors affecting trade in services have took their places among topics which are frequently researched in the literature. In this context, this paper discusses how informal economy, whch is affected by globalization process, influenced Turkish service export. This study is important because the number of researches examining the relationship between informal economy and Turkish service export is not sufficient and it broadens horizon in the road of improving Turkish service export. Within the scope of this study, a model which focuses on globalization, informal economy and international trade in services and includes additional variables, has been proposed and discussions have been conducted on this model. At the end of the study, suggestions were made about future studies related to this subject.

Küreselleşme hiç şüphesiz her alanda etkili olan bir olgudur. Bu bağlamda kayıt dışı ekonomi de küreselleşme sürecinden etkilenen alanlardan birisidir. Öte yandan özellikle 2000’li yıllardan sonra mal ve hizmet ticaretinin ayrı ayrı incelenmeye başlanmasıyla hizmet ticaretini etkileyen unsurlar literatürde sıkça araştırılan konular arasında yerini almıştır. Bu bağlamda bu çalışma küreselleşme sürecinden etkilenen kayıt dışı ekonominin Türk hizmet ihracatını nasıl etkilediğini tartışmaktadır. Literatürde kayıt dışı ekonomi ve Türk hizmet ihracatı arasındaki ilişkiyi inceleyen araştırma sayısının yetersiz olmasından ve Türk hizmet ihracatını geliştirme yolunda önemli ufuklar açmasından dolayı bu çalışma önemlidir. Bu çalışma kapsamında küreselleşme, kayıt dışı ekonomi ve hizmetin uluslararası ticaretine odaklanan ve yan değişkenler içeren bir model ileri sürülmüş ve bu model üzerinden tartışmalar yürütülmüştür. Ayrıca çalışma sonunda bu konu ile alakalı gelecekte yapılabilecek çalışmalar hakkında önerilerde bulunulmuştur.
KÜRESELLEŞME SÜRECİNDE KAYIT DIŞI EKONOMİNİN TÜRK HİZMET İHRACATI ÜZERİNDEKİ ETKİSİ ÜZERİNE MODEL ÖNERİSİ VE TARTIŞMA
Keywords: Economics; Ekonomi